Exogenous intoxication: Epidemiological analysis of reported cases in Alagoas, Brazil (Research, Society and Development, 2023)
Exogenous intoxication can be defined as contact or exposure to substances that are not part of our body. It is considered one of the most serious public health problems in the world. In Brazil, since 2016, it has become a notifiable condition. This study aimed to outline an overview of exogenous intoxications in the state of Alagoas, Brazil, between the years 2018 to 2022, and to analyze the behavior of the data during the pandemic period of COVID-19, with quantitative analysis. Data collection took place from DATASUS information system, a freely accessible database. A total of 16,227 cases of exogenous intoxication were notified in Alagoas during the studied period and the analysis of the data allowed us to conclude that exogenous intoxications are an essential public health problem in Alagoas and that there was a decrease in the number of notifications in the pandemic period of COVID-19.